2014
DOI: 10.1080/00223980.2014.881313
|View full text |Cite
|
Sign up to set email alerts
|

Hope, Anger, and Depression as Mediators for Forgiveness and Social Behavior in Turkish Children

Abstract: This study examined the mediating effects of hope, anger, and depression in the associations between forgiveness and social behavior, in fourth grade students in Turkey. The 352 fourth grade primary school students were involved in the study. The average age was 9.98 and 56.3% were boys. The Enright Forgiveness Inventory for Children (EFI-C), the Beck Anger Inventory for Youth (BANI-Y), the Children Hope Scale (CHS), the Social Behavior Questionnaire (SBQ), and the Children's Depression Inventory (CDI) were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
0
2
0
3
Order By: Relevance
“…Children who forgive are more accepted by their peers (van der Wal et al, 2017). Additionally, forgiveness has been shown to reduce anger among children and adolescents (Taysi et al, 2015; Watson et al, 2017).…”
Section: Effects Of Forgiveness and Anger On Children And Adolescentsmentioning
confidence: 99%
“…Children who forgive are more accepted by their peers (van der Wal et al, 2017). Additionally, forgiveness has been shown to reduce anger among children and adolescents (Taysi et al, 2015; Watson et al, 2017).…”
Section: Effects Of Forgiveness and Anger On Children And Adolescentsmentioning
confidence: 99%
“…Previous studies by Satici (2016), andTaysi et al (2015) have indicated Hope as a critical mediator between the psychological vulnerability of individuals and their affective well-being. Hope has also been proposed as a mediator in other emotions-related studies (Anjum et al, 2018;Shahid et al, 2023).…”
Section: Relationship Between Hope and Affective Well-beingmentioning
confidence: 98%
“…Από τον υπολογισμό των σκορ των προτάσεων προκύπτει μία κλίμακα για τη συγχώρεση (α πριν μέτρηση = ,96, α μετά μέτρηση = ,97) συνολικά και τρεις υποκλίμακες για τα συναισθήματα (α πριν μέτρηση = ,92, α μετά μέτρηση = ,95), τις συμπεριφορές (α πριν μέτρηση = ,83, α μετά μέτρηση = ,86) και τις σκέψεις (α πριν μέτρηση = ,92, α μετά μέτρηση = ,93) συγχώρεσης των ερωτώμενων. Το ερωτηματολόγιο παρουσιάζει ικανοποιητικό βαθμό εγκυρότητας σε σχολικές παρεμβάσεις για την συγχώρεση (Baskin & Enright, 2004· Enright et al, 2007 και υψηλό βαθμό εσωτερικής συνοχής σε παιδιά δημοτικού (Taysi, Curun, & Orcan, 2015). Στην παρούσα έρευνα οι δείκτες αξιοπιστίας alpha του Cronbach ήταν υψηλοί (α > 0,80) τόσο για την συνολική κλίμακα όσο και για τις υποκλίμακές της και στις δύο μετρήσεις.…”
Section: ερωτηματολόγιο συγχώρεσης του Enright γιαunclassified